A20 down-regulation promotes UVB-induced inflammation via activation of the NF-κB pathway. Issue 1 (April 2020) - Chen, Yan; Wu, Wenjuan; Li, Xing; Guo, Yanni; Lu, Fengyan; Man, Maoqiang; Jin, Yumei; Yang, Chunyan; Chai, Yanjie; He, Li
Highlights: A20 expression was decreased in CAD skin tissues and in UVB- irradiated HaCaT cells. Secretion of cytokines showed similar trends in CAD skin lesions and in UVB irradiated cells. A20 knock-down or over-expression altered secretion of inflammatory cytokines through the NF-κB pathway. Since UVB-induced inflammation is associated with A20, which could provide new insight into the discussion of skin inflammation related to CAD.